THE USE OF THE GAME " MATHEMATICAL DOMINO " IN BIOCHEMISTRY LESSONS - Yulduz Zikrulloyevna Rasulova (Scientific Impulse, 2024)
As an educational style, games perform the following tasks; * Educator-the formation of general education skills, the cultivation of creative abilities, including the explanation, identification and analysis of new situations.